Local genetic adaptation generates latitude‐specific effects of warming on predator–prey interactions. (15th December 2012) - De, Marjan; Pauwels, Kevin; Van Den, Maarten; De, Luc; Stoks, Robby
Abstract Temperature effects on predator–prey interactions are fundamental to better understand the effects of global warming. Previous studies never considered local adaptation of both predators and prey at different latitudes, and ignored the novel population combinations of the same predator–prey species system that may arise because of northward dispersal. We set up a common garden warming experiment to study predator–prey interactions between Ischnura elegans damselfly predators and Daphnia magna zooplankton prey from three source latitudes spanning >1500 km. Damselfly foraging rates showed thermal plasticity and strong latitudinal differences consistent with adaptation to local time constraints. Relative survival was higher at 24 °C than at 20 °C in southern Daphnia and higher at 20 °C than at 24 °C, in northern Daphnia indicating local thermal adaptation of the Daphnia prey. Yet, this thermal advantage disappeared when they were confronted with the damselfly predators of the same latitude, reflecting also a signal of local thermal adaptation in the damselfly predators. Our results further suggest the invasion success of northward moving predators as well as prey to be latitude‐specific. We advocate the novel common garden experimental approach using predators and prey obtained from natural temperature gradients spanning the predicted temperature increase in the northern populations as a powerful approach to gain mechanistic insights into how community modules will be affected by global warming. It can be used as a space‐for‐time substitution to inform how predator–prey interaction may gradually evolve to long‐term warming.